Business Environment, Competitive Advantage, and Firm Performance among Indonesian Small and Medium Enterprises: An Integrated Resource-Based and Dynamic Capability Perspective - Indra Jaya Nugraha; Isagani M. Tano; Epimaco A. Cabanlit, J. (PT. Mawadaku Sukses Solusindo, 2026)
Small and Medium Enterprises (SMEs) constitute the backbone of Indonesia's economic system by contributing substantially to employment generation, regional development, innovation, and inclusive economic growth. Despite their strategic importance, many Indonesian SMEs continue to experience persistent challenges associated with environmental uncertainty, limited organizational capabilities, technological disruption, increasing competitive intensity, and institutional constraints. These challenges require SMEs not only to adapt to changing business environments but also to develop sustainable competitive advantages capable of improving organizational performance over time. Drawing upon the Resource-Based View (RBV) and Dynamic Capability Theory (DCT), this study develops an integrated conceptual framework explaining how business environment influences SME performance directly and indirectly through competitive advantage. Unlike previous studies that primarily examine environmental factors as isolated antecedents of organizational performance, this study conceptualizes business environment as a multidimensional construct encompassing both internal organizational resources and external environmental conditions. Competitive advantage is proposed as the strategic mechanism through which SMEs transform valuable organizational resources and adaptive capabilities into superior market performance. The proposed framework highlights the strategic role of dynamic capabilities in sensing environmental opportunities, seizing emerging market potential, and continuously transforming organizational resources to sustain competitiveness in highly dynamic markets. This study adopts a quantitative explanatory research design involving Indonesian SMEs. Structural Equation Modeling using Partial Least Squares (PLS-SEM) is proposed to evaluate the hypothesized relationships among business environment, competitive advantage, and firm performance. Business performance is assessed using multidimensional indicators, including sales growth, market expansion, profitability, capital growth, and organizational sustainability. The study contributes theoretically by integrating Resource-Based View and Dynamic Capability Theory into a comprehensive model suitable for explaining SME competitiveness in emerging economies. Practically, the findings are expected to provide valuable managerial insights for SME owners and policymakers seeking to strengthen organizational resilience, enhance competitive positioning, and improve long-term business sustainability amid rapidly evolving economic conditions.